BGIG10116_34868: A Newly Discovered Gene Regulating Ejaculation Function - Gao, Jingjing; Gao, Rui; Li, Hu; Liu, Xi; Gao, Pan; Du, Junhua; Jiang, Hui; Zhang, Xiansheng (Frontiers in Physiology, 2022)
Ejaculation is a complex biphasic process involving a series of neurophysiological activities, such as the contraction of a large number of muscle groups and the ejaculation of semen from the urethra anterior. Due to the complexity of the process, many related factors have not been fully clarified, resulting in ejaculation dysfunction. As a common ejaculation dysfunction, lifelong premature ejaculation (LPE) is a problem for many people. Notably, gene polymorphism might play an important role in the etiology of LPE. However, the quest for identifying the actual genetic loci that contribute to LPE etiology has not been successful. Due to discrepancies in the design and methods of research, the correlation of most reports was not obtained in subjective replication experiments, and the conclusions may be inconsistent. In our study, three groups of ejaculation rats, namely, “rapid, normal, and delayed,” were selected based on the animal model of premature ejaculation (PE) in rats and the theory of ejaculation. Among them, the rats in the “rapid” ejaculation group can be used to stimulate humans with PE. Subsequently, we used the rat brain tissue for whole-transcriptome sequencing to screen the differential genes among the three groups. We tried to identify the actual genetic loci that contribute to PE etiology and provide a theoretical basis for the targeted therapy of PE.